2022
DOI: 10.2147/jaa.s340522
|View full text |Cite
|
Sign up to set email alerts
|

High Use of Antidepressant Medication in Both Mild-to-Modelate and Possible Severe Asthma – A Nationwide Cohort Study

Abstract: Purpose:In asthma, increased severity has been linked to depression assessed as assessed by patient-reported outcomes. However, little is known about predictors of antidepressant use in asthma compared to the background population. Methods:The study consists of 60,534 asthma patients aged 18-45 and a 1:1 age-and sexmatched control group. Using national registries and prescription data, the prevalence of and risk factors for antidepressant use were investigated by logistic regression adjusted for age, sex, work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Significant disparity by wealth status was found in 8/19 countries studied, with variation in the direction of the relationship between individual wealth and antidepressant. This finding is to some extent in line with previous studies; for instance, a study from Peru concluded that 62 individuals with lower levels of wealth were less likely to be treated for depression, 62 while a study from Denmark 63 indicated that having higher income was associated with lower odds of using antidepressants. 63 Our findings are likely to reflect the complex factors influencing the desirability of medication or psychological therapy as well as access that individual wealth could buy.…”
Section: Discussionsupporting
confidence: 90%
“…Significant disparity by wealth status was found in 8/19 countries studied, with variation in the direction of the relationship between individual wealth and antidepressant. This finding is to some extent in line with previous studies; for instance, a study from Peru concluded that 62 individuals with lower levels of wealth were less likely to be treated for depression, 62 while a study from Denmark 63 indicated that having higher income was associated with lower odds of using antidepressants. 63 Our findings are likely to reflect the complex factors influencing the desirability of medication or psychological therapy as well as access that individual wealth could buy.…”
Section: Discussionsupporting
confidence: 90%
“…Immunological [ 9 ] and genetic [ 10 ] theories, among others, have been suggested as possible explanations for this association. Furthermore, in a study by Akula et al [ 11 ], asthma was found to be linked with self-reported depressive symptoms, and the association between asthma and depression is further underlined by a significantly higher use of antidepressant medication in asthma patients compared to the general population, as reported by Håkansson et al [ 12 ]. The mechanisms linking asthma and depression have yet to be fully understood.…”
Section: Introductionmentioning
confidence: 94%
“…The REASSESS Young Adults cohort is based on public registries and has previously been described in detail. 5,44 However, due to limitations of the Danish National Database of Reimbursed Prescriptions prescribed doses of ICS are not available for research purposes and ICS doses are thus calculated as average daily exposure based on prescription redemption during the study period. While this integrates real-world adherence into the calculated ICS dose, GINA Treatment Steps are based on prescribed dose, and this should be kept in mind when performing direct comparisons to other cohorts.…”
mentioning
confidence: 99%